Lytic Lesion in the Proximal Humerus After a Flu Shot: A Case Report. Issue 3 (July 2019) - Erickson, Brandon J.; DiCarlo, Edward F.; Brause, Barry; Callahan, Lisa; Hannafin, Jo
Abstract : Case: There has been a recent campaign to vaccinate patients in an effort to prevent widespread flu pandemic. Although the complication rate after vaccine is low, there have been reports of Guillain-Barré syndrome and shoulder injury related to vaccine administration (SIRVA). In this case presentation, we discuss a patient who developed a large lytic lesion in the proximal humerus after a deeply administered flu shot. Conclusions: SIRVA is a rare cause of shoulder pain after injections, but one that progresses and often necessitates operative management. Clinicians should be wary of persistent shoulder pain after a flu shot.